Meaningful absence across arts and media : the significance of missing signifiers - Wolf, Werner, 1955-; Balestrini, Nassim Winnie; Bernhart, Walter (Studies in intermediality, 2019)
This volume focusses on a rarely discussed method of meaning production, namely via the absence, rather than presence, of signifiers. It does so from an interdisciplinary, transmedial perspective, which covers systematic, media-comparative and historical aspects, and reveals various forms and functions of missing signifiers across arts and media. The meaningful silences, blanks, lacunae, pauses, et cetera, treated by the ten contributors are taken from language and literature, film, comics, opera and instrumental music, architecture, and the visual arts. Contributors are: Nassim Balestrini, Walter Bernhart, Olga Fischer, Saskia Jaszoltowski, Henry Keazor, Peter Revers, Klaus Rieser, Daniel Stein, Anselm Wagner, Werner Wolf.